Angiography of testicular artery with special reference to the blood supply of the testis in camel - ANURADHA, ANURADHA; JAIN, R K; GUPTA, A N (The Indian Journal of Animal Sciences, 2014)
The right and left testicular arteries in camel arose independently from the ventrolateral aspect of abdominal aorta at the level of fourth or fifth lumbar vertebra. Both arteries although had different relations and course inside the abdominal cavity had similar inguinal and post inguinal course. The artery described a great number of convolutions in close apposition to each other, thus formed an elongated vascular cone with Its apex at the superficial inguinal nng and the base on the caputal extremity of the testis. As testicufar urtery reached caputal extremity of testis it showed 2 patterns In Its course. The intratesticular arborization of testicular artery consisted of centripetal and centrifugal arteries.